Air Quality Monitoring System based on the TI MSP430 Microcontroller Family - Kommey, Benjamin; Tamakloe, Elvis; Ato-Sam, Nathaniel; Agyekum, Kwame Agyeman-Prempeh (Universitas Sriwijaya, 2026)
Air quality monitoring devices are generally sensor circuits coupled with signal processing devices, where the output signal provides intelligible information to users. In this project report, a low-cost portable air quality monitoring device based on the TI MSP430G2553 microcontroller is described and designed. The device can monitor the air quality in one’s immediate environment and hence it gives individuals an idea of how clean or polluted the air in their surroundings is. A design is presented which applies basic gas sensing techniques and analog-to-digital conversion (ADC) principles to achieve the needed functionality. The device is built with off-the-shelf components, which are easy to comprehend and assemble. The device can detect the presence of ammonia (NH3), nitrogen oxides (NOx), benzene (C6H6), Carbon dioxide (CO2), smoke, and other hazardous gases and it is powered by a dc supply voltage ranging between +7V and +12V.